(untitled) (Tempo e Argumento, 2012)
Based on the analysis of empirical data from a series of educational activities in museum spaces, this article explores a series of factors which guide the use of museums in teaching history. We propose a methodology for a didactic use of the museum in the classroom that allows, first, the linking of the contents studied in the classroom with the exposure to be visited, and second, the realization of the visit jointly with a set schedule and, third, back to the classroom, the use of the museum experience to conduct a cultural product.